COVID-19 and the Fourth Burden of Women in Developing Countries: A Mini Review - Eyanoer, Putri C.; Zaluchu, Fotarisman (Open Access Macedonian Journal of Medical Sciences, 2020)
It is known that women experience heavier physical and psychological burdens more than men. This is closely related to the traditional role of women because of the absence of women’s authority in themselves. In the coronavirus disease (COVID)-19 pandemic situation, the role of women has increased, namely taking on a protective role. With this additional burden, the physical and psychological burden on women becomes heavier and has the potential to create health problems in the future. In this mini review, the authors discuss the potential impact of implementing the COVID-19’s prevention protocol on women’s lives. It was concluded that there were serious and very large potential consequences for women, in terms of physically, psychologically, or emotionally; thus, early anticipations are really needed.